Organoleptic Test of Rendang Made from Cashew Fruit Flesh - Tampubolon, Surya Elizabeth; Hendrayana, Made; Sunada, I Nyoman (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Cashew fruit flesh is one of the food ingredients that has good nutritional content for the body and can be processed into food ingredients, such as as a substitute for rendang meat. This study aims to utilize cashew fruit flesh as rendang through organoleptic tests reviewed from taste, texture, color and aroma. The data techniques used were experiments, documentation, questionnaires, and qualitative descriptive data analysis techniques using Likert scale calculations. The results of the study on the use of cashew fruit flesh as rendang in terms of taste were 89.6%, texture 80%, color 95.25% and aroma 92.8%. Then obtained an average result of the Likert scale analysis of 89.4% with very good interpretation criteria. Thus it can be concluded that cashew fruit flesh can be used as an alternative substitute for meat in rendang.